Pengamanan File Video dengan Enkripsi dan Deskripsi Menggunakan Algoritma Salsa20 dan RSA - I Putu Herdy Juniawan; I Komang Ari Mogi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
In the face of escalating security challenges in the advanced digital era, the exchange and storage of video files have become integral to daily life, impacting everything from business communication to personal entertainment. While the internet facilitates easy access to multimedia content, it also brings heightened risks of data theft and privacy breaches. Cryptography offers a solution by encrypting sensitive data. This research employs two encryption algorithms, Salsa20 and RSA, to protect video files. Salsa20 ensures fast and secure encryption, maintaining data integrity and confidentiality. RSA facilitates secure key exchange, limiting access to authorized recipients. The combined use of these algorithms effectively secures video files, guarding against data theft and privacy breaches. This offline encryption system offers flexible accessibility without compromising security. Additionally, it preserves the original file extension, adding an extra layer of protection, while decryption enables seamless access and playback of video content.